1980
DOI: 10.1159/000207279
|View full text |Cite
|
Sign up to set email alerts
|

On the Inhibitory Effect of the Serum of Uraemic Children on Erythropoiesis

Abstract: The erythropoietin activity and the erythropoiesis inhibiting factor(s) (EIF) were studied in the serum of 10 children and adolescents suffering from terminal renal insufficiency. The influence of haemodialysis on these factors was examined as well. As a test model for the estimation of erythropoietin activity and EIF we used hypertransfused polycythaemic mice. No erythropoietin activity was detectable in the serum of children and adolescents. A 40%-inhibitory effect on erythropoiesis existed in 8 out of 10 ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
1984
1984

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the earliest report, Markson & Rennie (19 5 6) found that when normal human marrow was cultured for 2 4 h in the presence of normal or uraemic serum, a relative decrease in the number of orthochromatic normoblasts was seen in the presence of uraemic sera (Fisher et al, 1 9 74). Inhibition of erythropoiesis in the presence of uraemic sera was confirmed in systems employing dog, rabbit and mouse target cells, by the polycythaemic mouse assay (Fisher et a], 1968; Scigalla et al, 1980), j9Fe incorporation into haem (Wallner et al, 1976-81). & Huang, 1980), and erythroid colony growth from CFU-E and BFU-E (Wallner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the earliest report, Markson & Rennie (19 5 6) found that when normal human marrow was cultured for 2 4 h in the presence of normal or uraemic serum, a relative decrease in the number of orthochromatic normoblasts was seen in the presence of uraemic sera (Fisher et al, 1 9 74). Inhibition of erythropoiesis in the presence of uraemic sera was confirmed in systems employing dog, rabbit and mouse target cells, by the polycythaemic mouse assay (Fisher et a], 1968; Scigalla et al, 1980), j9Fe incorporation into haem (Wallner et al, 1976-81). & Huang, 1980), and erythroid colony growth from CFU-E and BFU-E (Wallner.…”
Section: Discussionmentioning
confidence: 99%
“…Although inadequate erythropoietin (Ep) production is a major cause of anaemia in chronic renal failure (CRF) (Fisher, 1980;Cotes, 1982), uraemic toxins or inhibitors of erythropoiesis present in serum are also said to play a significant role in the development of the anaemia. Both in vivo (Fisher et al, 1968;Scigalla et al, 1980) and in vitro (Markson & Rennie, 1956;Fisher et al, 1974;Moriyama et al, 1975;Wallner et al, 1975Wallner et al, , 1976Wallner et al, , 1977Wallner et al, , 1978Wallner& Vautrin, 1978Urabeetal, 1976;Ohno&Fisher, 1977;Ohnoetal, 1978;Freedmanet al, 198 3 ) studies of uraemic sera have supported the concept that uraemic toxins accumulate in serum to suppress erythropoiesis, and that dialysis may remove these factors (Radtke et al, 1979(Radtke et al, , 1981Gutman & Huang, 1980: Wallner & Vautrin, 1981. Only a single study has been unable to demonstrate significant inhibition of erythropoiesis in vitro (Zucker et al, 1976).…”
mentioning
confidence: 99%